Facilitating networked learning with AI - Pedersen, Annette Q (Proceedings of the International Conference on Networked Learning, 2024)
The breakthrough of generative AI is disrupting education in many ways and universities and other educational institutions are tasked with navigating a host of new challenges. But in the classroom we might be seeing a familiar pattern: As with most new technologies in the classroom, there is a tendency to design exercises as individual tasks: AI as your personal tutor, AI as a Study Buddy, AI as your editor / idea generator / etc. However, if we believe that learners construct knowledge rather than just passively receive information, it is crucial that we discuss questions like these: How can we design good cooperative and collaborative learning environments for students? How can we design good exercises for with AI – considering that learning is not just transfer (or cramming) of information? How can we maintain a balance between AI assistance and human interaction in the learning environment? How can we encourage peer-to-peer learning and social engagement? How generative AI can enhance group discussions, facilitate idea generation, and support collaborative problem-solving? What are the best strategies to prevent the over-individualization of the learning process when incorporating generative AI? And not least: How can we best prepare teachers to use AI in their teaching? How can institutions best support teachers and students in this?